Genome-Wide Analysis of Major Facilitator Superfamily and Its Expression in Response of Poplar to Fusarium oxysporum - Jian Diao; Shuxuan Li; Ling Ma; Ping Zhang; Jianyang Bai; Jiaqi Wang; Xiaoqian Ma; Wei Ma (Frontiers in Genetics, 2021)
The major facilitator superfamily (MFS) is one of the largest known membrane transporter families. MFSs are involved in many essential functions, but studies on the MFS family in poplar have not yet been reported. Here, we identified 41 MFS genes from Populus trichocarpa (PtrMFSs). We built a phylogenetic tree, which clearly divided members of PtrMFS into six groups with specific gene structures and protein motifs/domains. The promoter regions contain various cis-acting elements involved in stress and hormone responsiveness. Genes derived from segmental duplication events are unevenly distributed in 17 poplar chromosomes. Collinearity analysis showed that PtrMFS genes are conserved and homologous to corresponding genes from four other species. Transcriptome data indicated that 40 poplar MFS genes were differentially expressed when treated with Fusarium oxysporum. Co-expression networks and gene function annotations of MFS genes showed that MFS genes tightly co-regulated and closely related in function of transmembrane transport. Taken together, we systematically analyzed structure and function of genes and proteins in the PtrMFS family. Evidence indicated that poplar MFS genes play key roles in plant development and response to a biological stressor.